Development of subsonic curved diffuser performance correlations integrated angle of turns using asymptotic computational fluid dynamics - Mohamed Rasidi, Shamsuri (2022)
Numerous studies on the performance of the curved diffuser have been made on either 2-D or 3-D expansion type with various working geometrical and operating parameters. Most researchers are focusing in the existence of flow separation phenomenon and secondary flow vortices that often disturb the recovery of pressure and uniformity of flow. On top of that, the existing guideline have just integrated the geometrical and operating effects in a low range. Therefore, the current work focussing on studying the effects of a wider turning angles in a range of 30° to 180° integrated with various operating condition by experiment and numerical method. The experimental rig was built at Aerodynamics Laboratory, UTHM. The blower speed was set in range of 9RPM-25RPM and tested for 30°, 90° and 180° curved diffusers. A profound set of Re